REVERSE CULTURE-SHOCK WITH AN ATTEMPT OF COMPROMISING CULTURES: A CRITIQUE OF A. RIHANI’S THE BOOK OF KHALID AND T. SALIH’S SEASON OF MIGRATION TO THE NORTH - Mugahed Alheshami; Mohammed Yassin Mohammed Aba Sha'ar (English Department of Faculty of Tarbiyah and Teacher Training, 2019)
Upon repatriation, many socio-psychological problems accompany the returnees to their home culture after spending a long time in the host culture. It is assumed that the returnees find no difficulty in re-adapting the life in their culture; however, many studies expound that re-adjustment in the home culture, particularly after spending a long time in another culture, is not an easy process, the returnees experience a re-entry or reversal cultural-shock. The main contention of this paper is to expound how Rihani and Salih attempt with a new literary trend to unify the eastern and western cultures in their fictional worlds. The paper underpins the idea of bridging the gaps between cultures and initiating a new era of mutual understanding and co-existence between the nations. It explicates how both novels present a different picture of the oriental world that contradicts with the orientalist and neo-orientalist depictions by projecting the Arabia culture and people equitably.